Social reproduction theory and the socialist horizon : work, power and political strategy - Jaffe, Aaron (Mapping social reproduction theory., 2020)
How do we integrate the theoretical underpinnings of Social Reproduction Theory (SRT) into our understanding of the social harms inflicted upon us? How can we use it to inform our struggles and affect societal change under capitalism?0Integrating our understanding of productive and reproductive spheres and exploring the connection between identity-based oppression and class exploitation, SRT has emerged as a powerful Marxist frame for social analysis and political practice. In this book, Aaron Jaffe extracts SRT's radical potential, relying on recent struggles, including the International Women's Strike and the teachers' strikes, showing how we can use SRT to motivate socialist politics and strategy.0Using Social Reproduction Theory to appreciate distinct forms of social domination, this unique and necessary book will have vital strategic implications for anti-capitalists, anti-racists, LGBT activists, disability activists and feminists.